AB0834 A Proposal of Definition of Early Symptomatic Knee Osteoarthritis (Eskoa). Results from an International Consensus Promoted by the Italian Society of Rheumatology (Sir). (9th June 2015) - Migliore, A.; Scirè, C.A.; Carmona, L.; Bizzi, E.; Damjanov, N.; Ionescu, R.; Rashkov, R.; Bablic-Nagic, D.; Collaku, L.; Denisov, L.; Barskova, T.; Martusevitch, N.; et al.
Abstract : Background: In the literature, no validated definition of Early Symptomatic Knee OsteoArthritis (ESKOA) is available. Objectives: The Italian Society of Rheumatology (SIR) organized an international consensus to provide a proposal of a definition of ESKOA. Methods: A set of focus groups were held with expert clinicians, basic science researchers, and patients in order to identify signs, symptoms, and risk factors of ESKOA. In parallel, a systematic literature reviewed the existing definitions of ESKOA. An international panel of experts, convened by the SIR, identified a set of disease constructs; these constructs underwent two Delphi rounds for prioritisation and weighting of items to include in a definition of ESKOA. Finally, during a face to face meeting, the panel agreed on a final proposal for the definition of ESKOA. Results: The systematic review failed to identify any validated definition of ESKOA. The focus groups identified 46 items, among risk factors, signs, and symptoms, which could reflect a pre-radiographic stage of knee OA. After the first expert meeting, these items were reduced to 15, then two Delphi rounds, by the weighting of items, led to the ranking of the criteria. A further evaluation led to a final definition of an algorithm for the identification of patients affected by ESKOA (Figure 1 ). Conclusions: The diagnosis of ESKOA is today possible and opens a relevant problem that is the identification of the therapeutic regimens needed to slow down disease progression. The early identification of ESKOA patients might allow a better quality of life significantly reducing the social and health systems costs. A validation study aimed to confirm the appropriateness of these criteria is warranted. Disclosure of Interest: None declared